The Wizard of Oz - Johnson, Richard (London Penguin Random House, 2019)
When Dorothy and her little dog Toto end up in the Land of Oz, they and their friends the scarecrow, tin man and cowardly lion have many adventures on their way to see the Wizard of Oz! Read it yourself with Ladybird is one of Ladybird's best-selling series. For over thirty-five years it has helped young children who are learning to read develop and improve their reading skills. Each Read it yourself book is very carefully written to include many key, high-frequency words that are vital for learning to read, as well as a limited number of story words that are introduced and practised throughout. Simple sentences and frequently repeated words help to build the confidence of beginner readers and the four different levels of books support children all the way from very first reading practice through to independent, fluent reading. Each book has been carefully checked by educational consultants and can be read independently at home or used in a guided reading session at school. Further content includes comprehension puzzles, helpful notes for parents, carers and teachers, and book band information for use in schools. The Wizard of Oz is a Level 4 Read it yourself title, ideal for children who are ready to read longer stories with a wider vocabulary and are keen to read independently
English Stories
For Children From 7 - 10 Years
Keywords: English stories